The Revolutionary Organisation : Armed Struggle from the Late 18th Century to the Present - Ree, Erik van (Social Sciences E-Books Online, Collection 2026., 2026)
This is the first comprehensive study of the phenomenon of the armed-struggle revolutionary organisation. The Revolutionary Organisation covers the period from the late 18th century to the present, is global in scope, and discusses organisations inspired by all main ideological traditions: communist, anti-colonialist, nationalist, democratic, Islamist, fascist, and white supremacist. The condition of life-and-death struggle with the state imposes similar patterns of operation upon these organisations, irrespective of their ideological inclinations. This work interprets armed-struggle revolutionary organisations as hybrids of three orientations: an apparatus of professional revolutionaries; an emotional community sustained by ideology, battle comradeship, and ritual; and an instrument of physical force nurturing an heroic organisational ethos.